5.2.13 Problems 1201 to 1300

Table 5.193: Second order linear ODE

#

ODE

Mathematica

Maple

6195

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+6 y = 0 \]

6196

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-16 y = 8 x^{4} \]

6197

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = x -\frac {1}{x} \]

6198

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = 2 x^{3} \]

6199

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 6 \ln \left (x \right ) x^{2} \]

6200

\[ {}x^{2} y^{\prime \prime }+y = 3 x^{2} \]

6201

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+y = 2 x \]

6202

\[ {}x^{2} \left (2-x \right ) y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

6203

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

6204

\[ {}x y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+\left (x +2\right ) y = 0 \]

6205

\[ {}3 x y^{\prime \prime }-2 \left (3 x -1\right ) y^{\prime }+\left (3 x -2\right ) y = 0 \]

6206

\[ {}x^{2} y^{\prime \prime }+\left (1+x \right ) y^{\prime }-y = 0 \]

6207

\[ {}x \left (1+x \right ) y^{\prime \prime }-\left (x -1\right ) y^{\prime }+y = 0 \]

6211

\[ {}r^{\prime \prime }-6 r^{\prime }+9 r = 0 \]

6213

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = 10 \,{\mathrm e}^{x}+6 \,{\mathrm e}^{-x} \cos \left (x \right ) \]

6215

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = x \]

6219

\[ {}x y^{\prime \prime }+y^{\prime } = 4 x \]

6220

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 26 \,{\mathrm e}^{3 x} \]

6221

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 2 \,{\mathrm e}^{-2 x} \cos \left (x \right ) \]

6222

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = 6 \,{\mathrm e}^{2 x} \]

6223

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = {\mathrm e}^{2 x} \]

6227

\[ {}y^{\prime \prime }-2 y^{\prime }+5 y = 5 x +4 \,{\mathrm e}^{x} \left (1+\sin \left (2 x \right )\right ) \]

6234

\[ {}y^{\prime \prime }+y^{\prime }-6 y = 6 \]

6243

\[ {}y^{\prime \prime } = -4 y \]

6245

\[ {}y^{\prime \prime } = y \]

6247

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 0 \]

6249

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+3 y = 0 \]

6251

\[ {}\left (x^{2}+2 x \right ) y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+2 y = 0 \]

6253

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

6255

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-2\right ) y = 0 \]

6388

\[ {}x^{\prime \prime }-\omega ^{2} x = 0 \]

6390

\[ {}x^{\prime \prime }+42 x^{\prime }+x = 0 \]

6393

\[ {}x^{\prime \prime }+2 \gamma x^{\prime }+\omega _{0} x = F \cos \left (\omega t \right ) \]

6394

\[ {}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{2 x} \]

6395

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 2 \cos \left (x \right ) \]

6396

\[ {}y^{\prime \prime }+16 y = 16 \cos \left (4 x \right ) \]

6397

\[ {}y^{\prime \prime }-y = \cosh \left (x \right ) \]

6407

\[ {}x \left (1+x \right )^{2} y^{\prime \prime }+\left (-x^{2}+1\right ) y^{\prime }+\left (x -1\right ) y = 0 \]

6408

\[ {}x \left (1-x \right ) y^{\prime \prime }+2 \left (1-2 x \right ) y^{\prime }-2 y = 0 \]

6409

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-9 y = 0 \]

6410

\[ {}x y^{\prime \prime }+\frac {y^{\prime }}{2}+2 y = 0 \]

6411

\[ {}x^{2} y^{\prime \prime }-x y^{\prime }+y = 0 \]

6412

\[ {}2 x y^{\prime \prime }-y^{\prime }+2 y = 0 \]

6413

\[ {}x y^{\prime \prime }+x y^{\prime }-2 y = 0 \]

6414

\[ {}x \left (x -1\right )^{2} y^{\prime \prime }-2 y = 0 \]

6417

\[ {}x y^{\prime \prime }+\left (1-x \right ) y^{\prime }+m y = 0 \]

6479

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 8 \]

6480

\[ {}y^{\prime \prime }-4 y = 10 \,{\mathrm e}^{3 x} \]

6481

\[ {}y^{\prime \prime }+2 y^{\prime }+y = {\mathrm e}^{-2 x} \]

6482

\[ {}y^{\prime \prime }+25 y = 5 x^{2}+x \]

6483

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 4 \sin \left (x \right ) \]

6484

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 2 \,{\mathrm e}^{-2 x} \]

6485

\[ {}3 y^{\prime \prime }-2 y^{\prime }-y = 2 x -3 \]

6486

\[ {}y^{\prime \prime }-6 y^{\prime }+8 y = 8 \,{\mathrm e}^{4 x} \]

6487

\[ {}2 y^{\prime \prime }-7 y^{\prime }-4 y = {\mathrm e}^{3 x} \]

6488

\[ {}y^{\prime \prime }-6 y^{\prime }+9 y = 54 x +18 \]

6489

\[ {}y^{\prime \prime }-5 y^{\prime }+6 y = 100 \sin \left (4 x \right ) \]

6490

\[ {}y^{\prime \prime }+2 y^{\prime }+y = 4 \sinh \left (x \right ) \]

6491

\[ {}y^{\prime \prime }+y^{\prime }-2 y = 2 \cosh \left (2 x \right ) \]

6492

\[ {}y^{\prime \prime }-y^{\prime }+10 y = 20-{\mathrm e}^{2 x} \]

6493

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 2 \cos \left (x \right )^{2} \]

6494

\[ {}y^{\prime \prime }-4 y^{\prime }+3 y = x +{\mathrm e}^{2 x} \]

6495

\[ {}y^{\prime \prime }-2 y^{\prime }+3 y = x^{2}-1 \]

6496

\[ {}y^{\prime \prime }-9 y = {\mathrm e}^{3 x}+\sin \left (x \right ) \]

6497

\[ {}x^{\prime \prime }+4 x^{\prime }+3 x = {\mathrm e}^{-3 t} \]

6498

\[ {}y^{\prime \prime }+4 y^{\prime }+5 y = 6 \sin \left (t \right ) \]

6499

\[ {}x^{\prime \prime }-3 x^{\prime }+2 x = \sin \left (t \right ) \]

6500

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = 3 \sin \left (x \right ) \]

6501

\[ {}y^{\prime \prime }+6 y^{\prime }+10 y = 50 x \]

6502

\[ {}x^{\prime \prime }+2 x^{\prime }+2 x = 85 \sin \left (3 t \right ) \]

6503

\[ {}y^{\prime \prime } = 3 \sin \left (x \right )-4 y \]

6504

\[ {}\frac {x^{\prime \prime }}{2} = -48 x \]

6505

\[ {}x^{\prime \prime }+5 x^{\prime }+6 x = \cos \left (t \right ) \]

6506

\[ {}y^{\prime \prime }-y^{\prime }-2 y = 4 x^{2} \]

6507

\[ {}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{3 x} \]

6508

\[ {}y^{\prime \prime }-y^{\prime }-2 y = \sin \left (2 x \right ) \]

6509

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 2 \sin \left (\frac {t}{2}\right )-\cos \left (\frac {t}{2}\right ) \]

6510

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 64 \,{\mathrm e}^{-t} \]

6511

\[ {}y^{\prime \prime }-6 y^{\prime }+25 y = 50 t^{3}-36 t^{2}-63 t +18 \]

6513

\[ {}y^{\prime \prime } = 9 x^{2}+2 x -1 \]

6514

\[ {}y^{\prime \prime }-5 y = 2 \,{\mathrm e}^{5 x} \]

6518

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x^{2}-1 \]

6519

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 4 \,{\mathrm e}^{2 x} \]

6520

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 4 \cos \left (x \right ) \]

6521

\[ {}y^{\prime \prime }-2 y^{\prime }+y = 3 \,{\mathrm e}^{x} \]

6522

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x \,{\mathrm e}^{x} \]

6529

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{x} \]

6530

\[ {}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{3 x} \]

6531

\[ {}x^{\prime \prime }+4 x = \sin \left (2 t \right )^{2} \]

6532

\[ {}t^{2} N^{\prime \prime }-2 t N^{\prime }+2 N = t \ln \left (t \right ) \]

6535

\[ {}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{x}}{x^{5}} \]

6536

\[ {}y^{\prime \prime }+y = \sec \left (x \right ) \]

6537

\[ {}y^{\prime \prime }-y^{\prime }-2 y = {\mathrm e}^{3 x} \]

6538

\[ {}y^{\prime \prime }-60 y^{\prime }-900 y = 5 \,{\mathrm e}^{10 x} \]

6539

\[ {}y^{\prime \prime }-7 y^{\prime } = -3 \]

6540

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{x}-\frac {y}{x^{2}} = \ln \left (x \right ) \]

6541

\[ {}x^{2} y^{\prime \prime }-x y^{\prime } = {\mathrm e}^{x} x^{3} \]

6546

\[ {}y^{\prime \prime }-y = 0 \]

6547

\[ {}y^{\prime \prime }-y = \sin \left (x \right ) \]

6548

\[ {}y^{\prime \prime }-y = {\mathrm e}^{x} \]